Nanoelectronics. Spin transport in the NEGF method and quantum spin Hall effect by «bottom-up» approach - Yu.A. Kruglyak; P.A. Kondratenko; Yu.М. Lopatkin (Журнал нано- та електронної фізики)
Spin transport with the NEGF method in the spinor representation, in particular, spin valve, rotating magnetic contacts, spin precession and rotating spins, Zeeman and Rashba spin Hamiltonians, quantum spin Hall effect, calculation the spin potential, and four-component description of transport are discussed in the frame of the «bottom – up» approach of modern nanoelectronics.